Clinical study of placenta previa and its effect on maternal health and fetal outcome - ., Sarojini; K. V., Malini; ., Radhika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: When the placenta is implanted partially or completely in the lower uterine segment it is called placenta previa. The objective of the study was to determine the incidence, obstetric risk factors, obstetric management, maternal mortality and morbidity, perinatal outcome in women presenting with placenta previa. Methods: Total 106 pregnant women with placenta previa were analyzed between January to December 2015. After applying the inclusion and exclusion criteria these women were analyzed with respect to their age, parity, gestational age and clinical features at presentation, history of warning bleeding, duration of hospitalization, need for blood transfusion, period of gestation at delivery, route of delivery and ICU admissions. For the newborn APGAR score, birth weight, need for NICU admission, still birth rate, neonatal mortality rate are noted down. Results: In this study 0.64% of the deliveries were complicated with placenta previa among them 23.6% women were above 30 years of age and 80.2% were multigravidas. 60.4% had major degree placenta previa, 36.8% had prior cesarean deliveries, 7.5% had prior abortion, 39.7% preterm deliveries. 85.8% cases delivered by cesarean delivery, 12.7% cases had postpartum haemorrhage and 4.7% had adherent placenta. There were 86.8% ICU admissions, 3.8% cases of acute kidney injury in present series. Conclusions: Advancing maternal age, multiparity, prior cesarean section, and prior abortions are independent risk factors for placenta previa. Placenta praevia remains a risk factor for adverse maternal and perinatal outcome. The detection of placenta previa should encourage a careful evaluation with timely delivery to reduce the associated maternal and perinatal complications.